The Use of UV-vis Spectroscopy Technique for Investigation of Organic Compounds in Saccharine Substrates - Mascarenhas, Maria do Socorro; Batistote, Margareth; Cardoso, Claudia Andrea Lima (Orbital: The Electronic Journal of Chemistry, 2022)
Sugar substrates are rich in organic compounds. However, its concentration may vary depending on the culture. Thus, the objective of this work was to evaluate the composition of sugarcane and sorghum juices using the UV-vis technique. An evaluation of the composition of the substrates was carried out and a pre-inoculum with YPSAC 5% medium, where 0.10 grams of FT858 yeast was inoculated and kept incubated at 30°C for 24h at 250rpm. The cells were recovered by centrifugation, resulting in a concentration of 10 mg mL-1 of wet mass that was inoculated into 50 mL of the previously prepared fermentation medium with a concentration of 22°Brix and pH 5.0. Aliquots were taken for evaluation of molecular absorption spectra using a spectrophotometer (Global Trade Technology). These substrates are composed of water and fermentable sugars. The evaluation of the molecular absorption spectra showed a difference in the profile of the substrates as well as in the subsequent hours of fermentation, with a decrease in the intensity of the peaks being observed that may be related to the absorption of nutrients by the yeast. vis shows promise for this type of analysis.